Effect of dietary fatty acid on blood lipid profile and induced bacterial infection in rat - Akter, Most Sumona; Yousuf, Md Abu; Ali, Md Yousuf; Khatun, Most Mahfuja; Saha, Sukumar; Islam, Md Kamrul (Asian Journal of Medical and Biological Research, 2015)
Ground nut is one of the commonly used decorative nutritious relish seed around the world. Ground nut have hypocholesterolamic, hypoglycemic, hypolipidemic, anti-atherosclerotic, immune-modulatory and bacterial counting effects. In Bangladesh, limited research has so far been performed on the action of ground nut in biological system and its comparative efficacy with commercialized drugs that reduce blood cholesterol. The aim of this study was carried on the effects of PUFA on blood total cholesterol (TC), high density lipoprotein (HDL), low density lipoprotein (LDL) and triglyceride (TG) and against artificial inoculation (I/N) Staphylococcus aureus infection of experimental rat by feeding of ground nut. A total of fifteen long Evans rats (Rattus norvegicus) were used for this study. The rats were randomly divided into three equal groups (n=5) and numbered as A, B and C. Group A (control), Group B (50gm ground nut/ day/group), group C (100 gm ground nut/day/group). All groups were supplied with standard broiler pellet and fresh drinking water throughout the experimental period (January to June /2012). The blood samples were collected directly from the heart at the 1st and 60th day for biochemical test (TC, LDL, HDL and TG) and test was performed as per Memorial Diagnostic Centre, Charpara, Mymensingh. Staphylococcus aureus was cultured in nutrient broth and 100 µl of their culture was inoculated into the rats through intranasal route. Among all the treated groups, the rats of group C exhibited the lowest TC value, TG and LDL and reduced blood cholesterol significantly than (control group A) followed by group B. In bacteriological examinations, it was found that the number of bacterial colony lowest in group C in comparison with the group of A and B. From the present experiment, it can be assumed that PUFA has significant effect on blood lipid profile and against bacterial infection. Asian J. Med. Biol. Res. June 2015, 1(2): 235-243